Potential Regenerative Capacity of physiological serum, L-arginine and IGF-1 on Skeletal Muscle - Naglaa Mohammed Alkalamawy (South Valley University, 2018)
In post-mitotic tissues such as skeletal muscles, there are no significant cell replacements throughout life; the cells sustain local damage through its pool of specified stem cells. Muscle satellite cells are mononuclear cells that remain in a quiescent state till be activated; when they proliferate and fuse with muscle fibers to donate myonuclei, a process necessary for post-embryonic growth, hypertrophy and tissue repair in this post-mitotic tissue. Modern trends in using (autologous) biological agents in the initiation of the regenerative process encourage us to evaluate the efficacy of some of these agents. In this study muscle damage was induced by cardiotoxin; followed by administration of biological agents; autologous physiological serum, L-arginine, and IGF-1 as a stimulating factor of myogenic satellite cells to initiate the myogenic regenerative process.